2014
DOI: 10.1371/journal.pone.0110645
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Treatment Managed by Providers outside the Public Health Department: Lessons for the Affordable Care Act

Abstract: IntroductionTuberculosis (TB) requires at least six months of multidrug treatment and necessitates monitoring for response to treatment. Historically, public health departments (HDs) have cared for most TB patients in the United States. The Affordable Care Act (ACA) provides coverage for uninsured persons and may increase the proportion of TB patients cared for by private medical providers and other providers outside HDs (PMPs). We sought to determine whether there were differences in care provided by HDs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…While the ACA could evolve to play a larger role in TB services, most notably the shift of TB care towards private medical providers (PMP), to date it has had little impact in this area [46]. However, a recent study concluded that TB patients under PMP care were less likely to receive the level of recommended care that TB cases routinely receive at public health departments such as directly observed therapy and documented culture conversion, cornerstones of public health practice with proven utility in stemming TB [47]. A major change in the public health system has been the constriction of funds for TB programs [48] due to the US economic crisis which was most intense in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…While the ACA could evolve to play a larger role in TB services, most notably the shift of TB care towards private medical providers (PMP), to date it has had little impact in this area [46]. However, a recent study concluded that TB patients under PMP care were less likely to receive the level of recommended care that TB cases routinely receive at public health departments such as directly observed therapy and documented culture conversion, cornerstones of public health practice with proven utility in stemming TB [47]. A major change in the public health system has been the constriction of funds for TB programs [48] due to the US economic crisis which was most intense in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Publications were from the USA [ 29 , 31 , 53 , 64 , 65 , 35 , 36 , 41 , 42 , 44 , 46 , 47 , 50 ], the UK [ 9 , 43 , 51 , 54 , 57 , 61 ], Spain [ 30 , 32 , 38 , 40 ], Japan [ 52 , 56 , 59 ], Turkey [ 37 , 48 , 63 ], Canada [ 34 , 62 ], Australia [ 39 ], Greece [ 49 ], Italy [ 45 ], the Netherlands [ 28 ], New Zealand [ 60 ], Norway [ 58 ], Saudi Arabia [ 66 ] and Switzerland [ 33 ]. One study was multi-national, participating countries being Armenia, Australia, Central African Republic, India, Philippines, South Africa, Swaziland, Uganda and the UK [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 publications on TB patient support, 36 included treatment supervision options [ 9 , 28 , 39 48 , 30 , 49 , 50 , 52 – 54 , 56 – 60 , 31 , 62 , 64 67 , 32 , 33 , 35 – 38 ] (19 as the sole patient support intervention [ 9 , 29 , 39 , 41 , 42 , 45 , 48 , 50 , 58 , 64 , 30 – 33 , 35 – 38 ]), 12 included SE support [ 34 , 43 , 61 , 62 , 46 , 47 , 52 , 53 , 56 , 57 , 59 , 60 ] (1 as the sole intervention [ 61 ]), 11 included PE support [ 34 , 40 , 62 , 51 , 53 – 57 , 59 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Due to data limitations we could not stratify our cost analysis by public versus private sector, which may be an important distinction. The impact of the changing health care system on the costs of TB care may be substantial, as some care traditionally provided by public health clinics shifts to primary care and community clinics [ 15 ]. Finally, this analysis did not take into account upward pressures on costs such as anti-TB drug shortages in the US [ 16 ].…”
Section: Discussionmentioning
confidence: 99%